Effect of Addition of a Specific Mixture of Yeast, Lactic and Acetic Bacteria in the Fermentation Process to Improve the Quality and Flavor of Cocoa Beans in Colombia - Jorge Daniel Fonseca Blanco; Martha del Pilar López Hernandez; Laura Sabrina Ortiz Galeano; Jenifer Criollo Nuñez; María Denis Lozano Tovar (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Cocoa fermentation process is fundamental to generate flavors and aromas that are characteristics of chocolate. In Colombia, this process is carried out by microbiota that spontaneously colonizes cocoa beans, therefore the quality of the fermentation is inconsistent. Taking into account that the fermentation of cocoa beans is carried out by a consortium of microorganisms, the aim of thisresearch was to describe the effect of the addition of a specific mixture of yeasts, acetic acid bacteria, and lactic acid bacteria on the physicochemical and organolepticcharacteristics of cocoa beans (clone CCN 51). Isolates of two yeasts (Wickerhamomyces anomalus and Debaryomyces hansenii), three acetic acid bacteria (AAB), (Gluconobacter japonicus, Acetobacter tropicalis, and Acetobacter pasteurianus) and three lactic acid bacteria (LAB) (Pediococcus acidilactici, Lactobacillus brevis, and Lactobacillus plantarum) obtained fromprevious cocoa fermentations selected for their pectinases and acid production capacities in a specific mixture were used. Using the micro-fermentation technique, the effect of a biological starter was evaluated under different viable microorganismsratios (Yeasts: LAB: AAB as follows, 1: 1: 1, 1: 2: 2, 1: 2: 1, 1: 1: 2, 2: 1: 1, 2: 2: 1, 2: 1: 2, and 2: 2: 2). The concentration of each microorganism was standardized at 1x107 cfu/mL, then the biomass of 4 mL for ratio 1 and 8 mL for ratio 2 of each suspension of microorganisms was added at time zero. Different doses of inoculum were 0%, 1%, 2%, 3%, 4%, and 5% v/w mL inoculum/g cocoa beans. A beneficial effecton the sensory quality of cocoa beans was evidenced by the addition of microorganisms; the best proportion of microorganisms was 2:1:2 (yeasts:LAB:AAB) and the best inoculum dose was 3% (v/w) showing lower acidity, astringency, and bitterness, and emphasizing the cocoa flavors, fruity, nutty, and panela malt.